2014
DOI: 10.1038/srep03757
|View full text |Cite
|
Sign up to set email alerts
|

Beyond radio-displacement techniques for Identification of CB1 Ligands: The First Application of a Fluorescence-quenching Assay

Abstract: Cannabinoid type 1 Receptor (CB1) belongs to the GPCR family and it has been targeted, so far, for the discovery of drugs aimed at the treatment of neuropathic pain, nausea, vomit, and food intake disorders. Here, we present the development of the first fluorescent assay enabling the measurement of kinetic binding constants for CB1orthosteric ligands. The assay is based on the use of T1117, a fluorescent analogue of AM251. We prove that T1117 binds endogenous and recombinant CB1 receptors with nanomolar affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
(83 reference statements)
0
26
0
Order By: Relevance
“…To rationalize SARs displayed by compounds 4e12 (Table 1), three-dimensional models of both CB1 and CB2 receptors were generated, as previously reported by us [42], by means of Modeller 9.11 software. Basically, the sphingoshine-1-phosphate type 1 receptor [S1P 1 (PDB code: 3V2Y)] was used as template because of both, the sequence identity percentage (27.03% and 24.16% for CB1 and CB2, respectively) and the close evolutionary relationship [43] (see Material and Methods).…”
Section: Molecular Modelling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To rationalize SARs displayed by compounds 4e12 (Table 1), three-dimensional models of both CB1 and CB2 receptors were generated, as previously reported by us [42], by means of Modeller 9.11 software. Basically, the sphingoshine-1-phosphate type 1 receptor [S1P 1 (PDB code: 3V2Y)] was used as template because of both, the sequence identity percentage (27.03% and 24.16% for CB1 and CB2, respectively) and the close evolutionary relationship [43] (see Material and Methods).…”
Section: Molecular Modelling Studiesmentioning
confidence: 99%
“…Three-dimensional models of both CB1 and CB2 receptors were generated through the Modeller 9.11 software [49] as previously reported by us [42]. Basically, the S1P 1 X-ray crystal structure (pdb code: 3V2Y [50]) was chosen and used as template to generate the 3D structure of both CB1 and CB2 receptors.…”
Section: Homology Modellingmentioning
confidence: 99%
“…Fluorescent‐based techniques, such as the development of fluorescently labeled ligands, are useful for analyzing peptide‐receptor interactions and binding kinetics . Furthermore they can help to elucidate the mechanisms of receptor trafficking and internalization, and could be used in the development of competition binding assays as a safer alternative to radioactive ligands . Despite their potential, few potent fluorescent ligands for class B GPCRs exist.…”
Section: Introductionmentioning
confidence: 99%
“…T1117 was then used as the competitive tracer in a binding assay, providing IC 50 values for anandamide and AM251 in agreement with literature values. Bruno et al (2014) further demonstrated utility of T1117 as a drug discovery tool by the appropriate identification of the CB 1 receptor allosteric ligand ORG27569 (Fig. 6).…”
Section: B Applications Of Small-molecule Fluorescent Toolsmentioning
confidence: 94%